Adaptasi Perubahan Iklim Pada Lahan Kering Sub Optimal Dengan Sistim Pola Tanam Usahatani Konservasi - Arief Budiyanto; Ishak Juarsah (STIPER Dharma Wacana Metro, 2018)
Increasing agricultural production can be done by planting a plot of land with various types of plants in a row or alternating cropping patterns. Agricultural cropping systems on dry land in the tropics have specific characteristics and depend on rainfall which can pose a threat to plant survival and the danger of erosion. . In suboptimal land with dry and wet climates, farmers generally plant upland rice alternately with corn and then plant beans. In reality, farmers do not only intercept/rotate between rice and secondary crops but also between crops and crops and/or crops and horticulture (vegetables). This paper aims to present research results related to efforts to increase land productivity by planting a plot of land with several types of plants to increase crop yields and farmers' income. The introduction of a conservation farming cropping system using ground cover and strip plants that produce organic matter is one of the alternatives to the conservation farming cropping system as well as for adaptation to climate change.